2011
DOI: 10.1111/j.1542-2011.2010.00018.x
|View full text |Cite
|
Sign up to set email alerts
|

Perineal Analgesia With an Ice Pack After Spontaneous Vaginal Birth: A Randomized Controlled Trial

Abstract: The use of ice packs for 20 minutes was effective for perineal pain relief after vaginal birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
16

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 11 publications
0
30
0
16
Order By: Relevance
“…Subjects in this study were randomized into three groups: the experimental group, composed of women who received an applica on of an ice pack for 20 minutes, the placebo group, composed of women who used a bag of water at room temperature, and the control group, composed of women who did not receive any interven on. The authors concluded that applying an ice pack for 20 minutes was eff ec ve at relieving perineal pain a er delivery (12) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Subjects in this study were randomized into three groups: the experimental group, composed of women who received an applica on of an ice pack for 20 minutes, the placebo group, composed of women who used a bag of water at room temperature, and the control group, composed of women who did not receive any interven on. The authors concluded that applying an ice pack for 20 minutes was eff ec ve at relieving perineal pain a er delivery (12) .…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, were included only 114 postpartum women underwent to cryotherapy: 38 women used ice for 20 minutes in the fi rst study (Group C) (12) and 76 women par cipated in the second trial. Of the 76 women in the second trial, 38 women used an ice pack for 10 minutes (Group A) and 38 women underwent cryotherapy for 15 minutes (Group B) (14) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During this first stage, the population was divided into three groups: experimental, which consisted of postnatal women who were administered an ice pack on the perineum for 20 minutes; placebo, in which a water pack at room temperature was used and control, which did not use the pack. The study concluded that use of the ice pack for 20 minutes was effective to relieve perineal pain after normal birth (Leventhal et al. 2011).…”
Section: Methodsmentioning
confidence: 99%